Trade and industrialization. - Deepak Nayyar(ed.) (Oxford, 1997)
Trade and Industrialization is part of the prestigious Themes in Economic analyses of problems related to the Indian economy. This collection of essays explores selected themes in trade and industralization the role of the state and the market in industrial development; consensus and disagreement on economic openness; linkages between trade, technology and growth; stock markets and the financing of corporate industrial trade and international investment in the process of industralization; and the implications of globalization for developing countries.
Keywords: Technology and development